2013
DOI: 10.4028/www.scientific.net/amr.791-793.949
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ceramic Material Crack Defect Based on the Ultrasonic Infrared Thermal Wave Technique

Abstract: For the needs of fast and efficient detection of crack defects of ceramic material, the ultrasonic infrared thermal wave method was applied for the research. Ultrasonic excitation is applied on a ceramic bowl which containing a crack defect, and the thermal infrared image of the crack was obtained by the thermal camera. The experimental results show that the ultrasonic infrared thermal wave method is suitable for the detection of crack damage of ceramic materials, and the detection speed is fast with a detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The results revealed the good detectability of this inspection; VT could detect a known fatigue crack of 0.015 mm in length with a better possibility of detection (POD) than the traditional method (15). In addition, VT was capably performed on various materials such as concrete (16,17), ceramics (18), polymers (19,20), and metals (21)(22)(23). The aforementioned studies confirmed the usability, rapidity, and variety of this inspection method.…”
Section: Introductionmentioning
confidence: 55%
“…The results revealed the good detectability of this inspection; VT could detect a known fatigue crack of 0.015 mm in length with a better possibility of detection (POD) than the traditional method (15). In addition, VT was capably performed on various materials such as concrete (16,17), ceramics (18), polymers (19,20), and metals (21)(22)(23). The aforementioned studies confirmed the usability, rapidity, and variety of this inspection method.…”
Section: Introductionmentioning
confidence: 55%
“…Consequently, many scholars started to utilize the vibrothermography to detect the defects in the materials. Initially, the vibrothermography was used to evaluate the cracks in the metal materials (Steel [17], Aluminum [18], Titanium and Inconel [19]) and ceramic materials [20]. Subsequently, this method was gradually utilized to detect composite materials as its application proceeding.…”
Section: Introductionmentioning
confidence: 99%